Gadolinia Doped Ceria Thin Films Prepared by Aerosol Assisted Chemical Vapor Deposition and Applications in Intermediate‐Temperature Solid Oxide Fuel Cells. Issue 5 (10th June 2013) - Schlupp, M. V. F.; Kurlov, A.; Hwang, J.; Yáng, Z.; Döbeli, M.; Martynczuk, J.; Prestat, M.; Son, J.‐W.; Gauckler, L. J.
Abstract Furthermore, deposition at such low temperatures is promising for processing of thin film assemblies. The preparation of bi‐layer electrolytes of yttria stabilized zirconia and gadolinia doped ceria thin films by aerosol assisted chemical vapor deposition is demonstrated. Gadolinia doped ceria films as thin as 150 nm are applied as barrier layers between yttria stabilized zirconia electrolyte and La0.6Sr0.4CoO3–δ cathode in anode supported solid oxide fuel cells. High power densities above 850 mW cm–2 at 650 °C are only obtained with these barrier layers, indicating that the GDC thin films effectively inhibit the formation of unwanted interface reactions.